Review of the occurrence of the oriental hornet Vespa orientalis Linnaeus, 1771 in the islands of Greece (Hymenoptera: Vespidae: Vespinae) - Ceccolini, Filippo (ENTOMOLOGIA HELLENICA, 2022)
Records of Vespa orientalis Linnaeus, 1771 for 28 islands of Greece are given: in 18 islands (Agistri, Euboea, Folegandros, Kalamos, Kalymnos, Karpathos, Kos, Leros, Lefkada, Naxos, Nisyros, Paros, Patmos, Pserimos, Telendos, Tilos, Tinos, Sifnos), these occurrences are the first record of the species for them. The total number of Greek islands in which V. orientalis is known becomes 33.